Commencement, Northeast Missouri State Teachers College, Kirksville, Mo., May 26, 1949 - Northeast Missouri State Teachers College (Kirksville, Mo.) (1949)
This commencement program shows the class roll on May 26, 1949 at the Northeast Missouri State Teachers College in Kirksville, MO.